Acupuncture Reduced the Risk for Insomnia in Stroke Patients: A Propensity-Score Matched Cohort Study - Qiu, Xuan; Han, Nan Sheng; Yao, Jie Xiao; Yu, Fang Rui; Lin, Yan Yan; Zhuang, Xun (Frontiers in Aging Neuroscience, 2021)
Abstract: Background:post-stroke insomnia (PSI) affects the quality of life of stroke patients, impairs the rehabilitation ability.At present, there was a certain understanding of the risk factors of PSI, but there was a lack of exploration of the protective factors of it. This article aims to analyze the relationship between acupuncture and insomnia in the stroke patients and explore the preventive treatment of acupuncture Method: Patients diagnosed with stroke from 2010 to 2019 from the case database of the First Affiliated Hospital of Guangzhou University of Chinese Medicine were selected , and followed up until 2020, according to factors such as gender, age, stroke type, stroke location, baseline comorbidities, A 1:1 propensity score was used to match an equal number of patients in acupuncture and non-acupuncture cohorts (N = 1680).We used Cox regression model and Kaplan-Meier method to estimate the risk of insomnia in the outcome event. Results: Compared with the non-acupuncture cohort, in general, stroke patients receiving acupuncture treatment had a lower risk of insomnia after adjusting for age, gender, stroke type, stroke location, and comorbidities [adjusted hazard ratio (HR)=0.27,95% confidential interval=(0.23-0.32)].For different genders, acupuncture also reduced the risk,The respective risks were male (adjust HR=0.28) and female (adjust HR=0.26).Acupuncture also lowered the risk of different age groups.As for the type of stroke, regardless of the ischemic, hemorrhagic or mixed of two type stroke, patients who received acupuncture showed a lower risk (adjusted HR = 0.28, 0.17 and 0.49, respectively). With regard to the location of stroke, except for the cerebral hemisphere, whether it was the frontal lobe,the basal ganglia, the radiation crown, the diencephalon or multiple partial strokes, the risk of receiving acupuncture was lower. For all baseline complications, acupuncture reduced the risk of outcome indicators (insomnia) Limitations : we did not classify the severity of post-stroke insomnia and did not provide specific acupuncture points. Finally, the sample size was inadequate,which still need to expand the sample size to strengthen the conclusion Conclusion: Acupuncture treatment reduced the risk of insomnia in stroke patients. Future research should expand the sample size and further elaborate the treatment mechanism of acupuncture